Making a Home in the Taiga: Movements, Paths and Signs among Orochen-Evenki Hunters and Herders of Zabaikal Krai (South East Siberia) - Donatas Brandišauskas (Journal of Ethnology and Folkloristics)
In this article, I will explore interrelations between place making, movement, use of paths and signs among the Orochen of Zabaikal Krai (Province). Although under the Russian Tsars Orochen-Evenki hunters and herders were referred to negatively as wanderers; today my ethnography demonstrates how movements of animals and humans are crucial for the success of their subsistence, place making and worldview. Hence, walking in the taiga is an important skill that is essential to hunting and herding activities when humans strive to identify animals' 'living places' (Orochen bikit) by reading their tracks and movements. Humans also leave their own tracks and paths as well as signs communicating with each other while subsisting in remote areas, in this way creating their own living places. Thereby, I show how movements and the use of paths is an important dimension of Orochen-Evenki wellbeing as well as their moral code.